2020
DOI: 10.1371/journal.pone.0240465
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, morbidity and clinical care in a referral neonatal intensive care unit in Haiti

Abstract: Background Neonatal mortality rates in Haiti are among the highest in the Western hemisphere. Few mothers deliver with a skilled birth attendant present, and there is a significant lack of pediatricians. The neonatal intensive care unit (NICU) at St. Damien Pediatric Hospital, a national referral center, is one of only five neonatology departments in Haiti. In order to target limited resources toward improving outcomes, this study seeks to describe clinical care in the St. Damien NICU. Methods A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
5
0
8
Order By: Relevance
“…Despite the frequent history of a variety of adverse obstetrical outcomes, the initial interview showed that most of these complications in fact occurred in their country of origin (most often Haiti). The literature on obstetrical and neonatal complications in Haiti is very poor, but there is a significant morbidity and mortality rate, particularly related to acute complications during pregnancy (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the frequent history of a variety of adverse obstetrical outcomes, the initial interview showed that most of these complications in fact occurred in their country of origin (most often Haiti). The literature on obstetrical and neonatal complications in Haiti is very poor, but there is a significant morbidity and mortality rate, particularly related to acute complications during pregnancy (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…This study assessed the neonatal outcomes at a newly formed neonatal care unit in southern Haiti and showed overall mortality of 12.2% during the first 2 years of the unit’s operation. This mortality rate is midrange compared to mortality rates that have been reported in similar settings elsewhere, including southern Eritrea (6.5%), western Ethiopia (8.8%), north-central Nigeria (13.4%), western Haiti (14.5%), south-eastern Nigeria (19.4%), eastern Ethiopia (20.0%), Ghana (20.2%), and southern Ethiopia (25.0%) [ 6 , 30 36 ]. If we exclude those who left the hospital early or were transferred out, we calculate a mortality rate of 15.7% among those with a known hospital outcome.…”
Section: Discussionmentioning
confidence: 66%
“…The lack of appropriate prenatal care, the low quality of obstetric care, and high rates of eclampsia, obstructed labor, untreated infection, and preterm delivery are persistent factors behind the high rates of maternal and neonatal mortality in Haiti [ 6 , 7 , 17 , 18 ]. In a recent analysis, we reported that 2–5% of deliveries in hospitals in southern Haiti suffered from eclampsia, which was likely an underestimation due to poor diagnostic capacity and data quality [ 19 ]; an eclampsia rate of 23% was reported in another Haitian hospital with better electronic record-keeping [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Já com relação ao tipo de parto, a maior parte dos estudos identificou que o parto cesáreo foi o mais utilizado (Barbosa et al, 2021;Valcin et al, 2020;Yang & Meng, 2020;Prestes et al, 2019;Umran & Jammali, 2017;Costa et al, 2017). Desses, segundo os estudos de Yang & Meng (2020) e de Umran e Jammali (2017), a maioria ocorreu de forma eletiva, sendo 56% e 65%, respectivamente.…”
Section: Aspectos Do Nascimento Dos Neonatos Internados Em Unidade De...unclassified
“…No entanto, também não receberam o contato pele a pele e aleitamento na 1º hora de vida (Pitilin et al, 2021). Enquanto, segundo Valcin et al (2020) o número de RNs que recebeu leite materno foi maior do que os que o receberam associado à fórmula ou aqueles que receberam somente a fórmula.…”
Section: Aspectos Do Nascimento Dos Neonatos Internados Em Unidade De...unclassified